2015
DOI: 10.1097/md.0000000000001402
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Survival Outcomes of Colorectal Cancer in Young Versus Elderly

Abstract: The incidence of colorectal cancer (CRC) in young adults is rising. We aimed to analyze the clinicopathological characteristics and survival outcomes of young versus elderly CRC patients. All patients diagnosed with CRC in the Surveillance, Epidemiology, and End Results program data (1988–2011) from the United States were evaluated. They were divided into 3 groups by age at diagnosis: group 1 (20–40 years old), group 2 (41–50 years old), and group 3 (>50 years old). The clinicopathological characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
6
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 20 publications
7
52
6
1
Order By: Relevance
“…Looking at the age at diagnosis, patients with CRC below the age of 50 years had the most favorable overall and stage-adjusted survival, although they had the highest proportion of stage III and stage IV cancers. Better or equal prognosis of younger than older patients, even when presenting at later stages and with more aggressive tumors, has been previously reported [41][42][43].…”
Section: Discussion In the Context Of The Literaturementioning
confidence: 73%
“…Looking at the age at diagnosis, patients with CRC below the age of 50 years had the most favorable overall and stage-adjusted survival, although they had the highest proportion of stage III and stage IV cancers. Better or equal prognosis of younger than older patients, even when presenting at later stages and with more aggressive tumors, has been previously reported [41][42][43].…”
Section: Discussion In the Context Of The Literaturementioning
confidence: 73%
“…Conversely, some smaller studies have not identified any age-related differences in histology or stage of disease between different age groups [17,30]. Some authors have suggested that the higher rate of advanced disease seen in the younger patient groups could be attributed to delayed diagnosis because: (1) younger patients are more likely to dismiss red-flag bowel symptoms and (2) physicians are less likely to refer young patients for endoscopic investigations, attributing their symptoms as benign [11,22,31]. Dozois et al [32] suggested maintaining a high index of suspicion when assessing young patients with abdominal symptoms because the majority of patients with CRC in their study were symptomatic at the time of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Table IV shows the 5-year observed and relative survival by age group (15-34, 35-44, 45-54, 55-64, 65-74, and 75+) for all the major cancer sites. Relatively higher survival rates were observed in younger patients (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) compared with older patients (65-74, 75+), particularly for sites including the stomach, lung, pancreas, B and CNS, blood (NHL) and cervix. Cancer of the oesophagus, female breast and bladder had higher survival in middle-aged groups (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)…”
Section: Resultsmentioning
confidence: 99%
“…the prognosis of cancer, but these included only a short time period (13,14), or site-specific survival from population based data (15)(16)(17). For providing a long-term assessment of population-based cancer data, this paper provides a systematic analysis of cancer survival for the period of 1972-2011 in Qidong, China.…”
Section: Cancer Survival In Qidong Between 1972 and 2011: A Populatiomentioning
confidence: 99%